Sistem Informasi Pengolahan Data Nilai Mahasiswa pada Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Pacitan - Aisyiyah, Nurul Robby; ., Sukadi (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2012)
Processing all data and information needs for both internal and external demand is still done manually, so the performance of data processing systems and other value is not optimal. On the progress of higher education requires a careful arrangement of the whole system, quick, and powerful, this requirement can be met with both if available a complete and accurate information in a variety of trusted sources of information is one of them by means of computerized systems in these activities. This study aimed to establish the points of data processing information systems students. This study will describe each stage of system development including analysis, design, and implementation of data processing information system of values. The results of this study allows the user to be able to manage data processing and studentsâ point. Keywords : Processing, Data, Points Library : 6